The Effect of Dual-Hemisphere Transcranial Direct Current Stimulation Over the Parietal Operculum on Tactile Orientation Discrimination - Fujimoto, Shuhei; Tanaka, Satoshi; Laakso, Ilkka; Yamaguchi, Tomofumi; Kon, Noriko; Nakayama, Takeo; Kondo, Kunitsugu; Kitada, Ryo (Frontiers in Behavioral Neuroscience, 2017)
The parietal operculum (PO) often shows ipsilateral activation during tactile object perception in neuroimaging experiments. However, the relative contribution of the PO to tactile judgment remains unclear. Here, we examined the effect of transcranial direct current stimulation (tDCS) over bilateral PO to test the relative contributions of the ipsilateral PO to tactile object processing. Ten healthy adults participated in this study, which had a double-blind, sham-controlled, cross-over design. Participants discriminated grating orientation during three tDCS and sham conditions. In the dual-hemisphere tDCS conditions, anodal and cathodal electrodes were placed over the left and right PO. In the uni-hemisphere tDCS condition, anodal and cathodal electrodes were applied over the left PO and contralateral orbit, respectively. In the tDCS and sham conditions, we applied 2 mA for 15 min and for 15 sec, respectively. Computational models of electric fields during tDCS indicated that the strongest electric fields were located in regions in and around the PO. Compared with the sham condition, dual-hemisphere tDCS improved the discrimination threshold of the index finger contralateral to the anodal electrode. Importantly, dual-hemisphere tDCS with the anodal electrode over the left PO yielded a decreased threshold in the right finger compared with the uni-hemisphere tDCS condition. These results suggest that the ipsilateral PO inhibits tactile processing of grating orientation, indicating interhemispheric inhibition of the PO.